PENGARUH ROLLING MASSAGE TERHADAP KELANCARAN PRODUKSI ASI IBU POST PARTUM PRIMIPARA DI DESA CAMPOR KEC. GEGER KAB. BANGKALAN) - ULVA NOVIANA (NHM PRESS, 2018)
Production of breast milk (ASI) wich is little and is not smooth one day after dilivery becomes an obstacle of early breastfeeding forpost partum primipara. Of 6 post partum primipara. 3 underwent breasr milk wich did not come out and 2 underwent breasr milk wich did not flow out smoothly and 1 underwent smooth flow of breast milk. This research was aimed to find aout the effects of rolling massage on smoothness of breast milk production for post partum primipara.This research employed pre-eksperiment, one group pretest-posttest design. Population consisted of post partum primipara and sample which used a porposive sampling technique consisted of 13 post partum primipara. The result showed that before treatment, 69.2% post partum priipara had unsmooth production of breast milk and only 30.8% post partum primipara had smooth production of breast milk and after treatment, 77% post partum primipara had smooth production of breast milk and only 23% post partum primipara had unsmooth production of breast milk.